Big Data Revolution: Enhancing Financial Planning and Budgeting Strategies - Darwish, Nawal Y. Abu; Alqhzzawi, Ali M.; Alqisi, Emad I.; Shkoor, Amer S. (Future Science / FSH-PH Publications, 2025)
Companies leverage big data in accounting to enhance decision-making processes, thereby increasing the efficiency and effectiveness of budgeting and financial planning. By analyzing vast amounts of da-ta, businesses can gain insights into customer behavior, develop strategies to improve customer experience, make accurate forecasts of financial results, and refine their planning and budgeting processes. This study employs a dynamic data model to accurately estimate the relationships between various financial variables, with a particular focus on analyzing key performance indicators. The goal is to achieve consistency and reliability in the results, ultimately contributing to more informed and strategic financial decisions.The findings of this study suggest that the integration of big data analytics in financial planning and budgeting leads to improved accu-racy in financial forecasts, enhanced ability to identify and mitigate financial risks, and better alignment of budgeting processes with strategic business objectives. Additionally, companies that utilize big data are found to have a competitive advantage in terms of opera-tional efficiency and customer satisfaction. These insights underscore the transformative potential of big data in revolutionizing financial management practices.